The Effect of the American Embargo, 1807-1809, on the New England Cotton Industry - Ware, Caroline F. (Quarterly Journal of Economics, 1926)
The papers of the firm of Almy and Brown. — The firm's business prosperous in 1801–1807, 675. — The Embargo dealt a heavy blow, 677. — Yet many new mills built in 1808–1809, 681. — The practice of price-maintenance suggested as an explanation of the growth, 682. — New markets in the West and South after the Embargo, 686. — Conclusions, 688.